Encyclopedia of Inorganic and Bioinorganic Chemistry 2014
DOI: 10.1002/9781119951438.eibc0197.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Selenium: Inorganic Chemistry

Abstract: Selenium is the first member of the group 16 elements O, S, Se, Te, and Po that shows some metallic character. The increasing metallic character in the series O, S, Se, Te, Po is reflected also in the lower electronegativity, in the less acid character of the oxides, and in the lower stability of the oxidation number +VI for selenium compared to sulfur. There is a large variety of compounds of SeII, SeIV, and SeVI with the electronegative elements N, O, F, Cl, and Br. Thus, there are several types of compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 92 publications
0
5
0
Order By: Relevance
“…Although [SeOCl 2 ] is not anionic, a higher reactivity can be expected than that of [H 2 SeO 4 ]. 1 A previous study using TBP also showed that TBP did not extract [H 2 SeO 4 ], but instead it extracted [SeOCl 2 ] and [H 2 SeOCl 4 ]. 9 …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Although [SeOCl 2 ] is not anionic, a higher reactivity can be expected than that of [H 2 SeO 4 ]. 1 A previous study using TBP also showed that TBP did not extract [H 2 SeO 4 ], but instead it extracted [SeOCl 2 ] and [H 2 SeOCl 4 ]. 9 …”
Section: Resultsmentioning
confidence: 98%
“…Although [SeOCl 2 ] is not anionic, a higher reactivity can be expected than that of [H 2 SeO 4 ]. 1 A previous study using TBP also showed that TBP did not extract [H 2 SeO 4 ], but instead it extracted [SeOCl 2 ] and [H 2 SeOCl 4 ]. 9 Regarding the protonated structure of EHBAA, 21 an H + is chelated by two amide oxygen atoms and an amine nitrogen atom, and a Cl − weakly bonds to an array of polarized C-H d+ units on the opposite side of EHBAA from the protonation site.…”
Section: Extraction Mechanism Of Se(iv) and Se(vi)mentioning
confidence: 98%
See 1 more Smart Citation
“…We take a value of 4 for n throughout the whole theoretical calculations, which is attributed to the fact that Se 4 2+ exhibits a stable square planar ring structure compared to other cluster ions (Se 2 2+ , Se 8 2+ , and Se 12 2+ ). 53 While the reactions for the MoSe 2 electrode are the reversible redox processes of Se species mediated by Mo species (Fig. 5c).…”
Section: Resultsmentioning
confidence: 99%
“…5b ). 53 While the reactions for the MoSe 2 electrode are the reversible redox processes of Se species mediated by Mo species (Fig. 5c).…”
Section: Paper Energy and Environmental Sciencementioning
confidence: 99%